2012
DOI: 10.1055/s-0032-1312831
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Consensus Recommendations for the use of Vacuum-Assisted Breast Biopsy under Sonographic Guidance: First update 2012

Abstract: The VB is a safe method for extracting breast tissue for histological workup. The technique allows the resection of breast tissue up to 8 cm3. Besides the diagnostic indications, the method qualifies for a therapeutic resection of symptomatic benign lesions (e. g. fibroadenomas). The technique should be used in specialized breast centers working in a multidisciplinary setup. This paper is an expert's recommendation for the use of VB under sonographic guidance. It is not formulated as a nationwide guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 12 publications
0
47
1
7
Order By: Relevance
“…Unfortunately, we did not record procedure durations in our study. However, the procedure took around 30 minutes on average, as reported in the literature (8).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Unfortunately, we did not record procedure durations in our study. However, the procedure took around 30 minutes on average, as reported in the literature (8).…”
Section: Discussionmentioning
confidence: 75%
“…Especially in lesions smaller than 2 cm in size, success rates of 95-100% are reported. The method provides significant time and cost savings (8). Unfortunately, we did not record procedure durations in our study.…”
Section: Discussionmentioning
confidence: 96%
“…Due to fluid surrounding intraductal processes, ultrasonography of the ducts is very sensitive in uncovering such lesions. If pathological discharge correlates with a sonographically detected lesion, such lesions can be reliably diagnosed by vacuum biopsy [24]. …”
Section: Discussionmentioning
confidence: 99%
“…In view of the large sample size which a VAB device can collect, and as multiple samples can be retrieved at each intervention, it is feasible to completely excise breast lesions. The most commonly targeted lesions have been fibroadenomas and numerous studies have now been reported utilizing VAB as an alternative to surgical excision for the management of fibroadenomata 10,11 . Most studies have reported very high success rates with residual or recurrent lesions found in less than 10-15% of cases.…”
Section: The Changing Role Of Vacuum Assisted Biopsy Of the Breastmentioning
confidence: 99%